An Image Processing System for the Analysis of Gel Electrophoresis - Engelmann, U.; Meinzer, H. P. (Methods of Information in Medicine, 1984)
In medical and biological research considerable information is gained with regard to the molecular weight and the purity of samples with the aid of Polyacrylamid (PAGE) or agarose gel electrophoresis (AGE). The resulting gel images are usually evaluated by the scientists manually.Here we want to present procedures permitting an analysis of the images with the computer. The given tasks were solved using the interpreter PIC. PIC is an image processing system developed at the German Cancer Research Center. The latter was extended by special routines in the form of new commands, thus creating a modular, easy-to-use system.
Keywords: Image Processing; Interactive Language; Gel Electrophoresis